2021
DOI: 10.1093/pubmed/fdab024
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity as a companion virtue in response to the COVID-19 pandemic

Abstract: This paper establishes that there is a need to turn to virtue ethics in dealing with the COVID-19 pandemic. It argues that the virtue of solidarity can be a companion virtue to compassion for medical frontline workers and other individuals involved. Like compassion, the virtue of solidarity is a reminder that everyone is in this crisis together and that each is responsible for all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…This mirrors a well-known divide in public health ethics: individualistic versus communal considerations [6]. Particularly in the context of epidemics and pandemics, public health scholars have called for relational, solidaristic views on public health ethics [7,8], especially in the global health context [9]. At the beginning of the COVID-19 pandemic in Spring 2020, scientific evidence for the effectiveness on the general, broad use of face masks was lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This mirrors a well-known divide in public health ethics: individualistic versus communal considerations [6]. Particularly in the context of epidemics and pandemics, public health scholars have called for relational, solidaristic views on public health ethics [7,8], especially in the global health context [9]. At the beginning of the COVID-19 pandemic in Spring 2020, scientific evidence for the effectiveness on the general, broad use of face masks was lacking.…”
Section: Introductionmentioning
confidence: 99%
“…People often rely on solidarity to hold society together when faced with a crisis. In pandemics specifically, people need to support each other to get through a period when a virus threatens not just their physical health but also their mental health and social well-being (Ho & Dascalu, 2020;Galang et al, 2021). Similarly, the analysis of the items of the scale developed in this study showed that people tend to help others in every way that they can.…”
Section: Discussionmentioning
confidence: 68%
“…In a recent correspondence published in this journal, the authors surveyed the sudden engenderment of community pantries in the Philippines as a way of filling the gaps that is supposed to be coming from the government. 1 They also highlighted in another related correspondence that the virtue of solidarity can be our companion to get through this pandemic, 2 and these pantries are definitely an expression of the said virtue. I definitely support the idea of this great initiative from the public and that it was indeed a showcase of Filipino solidarity in times of crisis.…”
Section: To the Editormentioning
confidence: 99%